2016
DOI: 10.5603/cj.a2016.0021
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Tp-e interval and Tp-e/QT correlates well with modified Rodnan skin severity score in patients with systemic sclerosis

Abstract: Background: Ventricular arrhythmias can be seen in systemic sclerosis (SSc) p = 0.032) and p = 0.007, respectively) p = 0.001) and p = 0.001). p = 0.001) and CRP (b = 2.273, p = 0.027) were found to be significant independent predictors of p = 0.001) (Cardiol J 2016; 23, 3: 242-249)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…In addition, significant correlations between modified Rodnan skin severity score (used to assess extent and severity of skin involvement in systemic sclerosis) and Tp-e as well as Tp-e/QT ratio were demonstrated. 35 However, in our SLE patients, both uncorrected and corrected Tp-e and Tp-e/QT values were not associated with SLICC/ACR-DI.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, significant correlations between modified Rodnan skin severity score (used to assess extent and severity of skin involvement in systemic sclerosis) and Tp-e as well as Tp-e/QT ratio were demonstrated. 35 However, in our SLE patients, both uncorrected and corrected Tp-e and Tp-e/QT values were not associated with SLICC/ACR-DI.…”
Section: Discussioncontrasting
confidence: 58%
“…21 Cardiac disease in SSc has been shown to be associated with skin fibrosis. 22,23 More patients with diffuse versus limited SSc demonstrate heart disease attributable to SSc. 24,25 Moreover, incident cardiomyopathy, symptomatic pericarditis, or an arrhythmia requiring treatment developed in 15% of 953 SSc patients with diffuse skin disease during a mean follow-up of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the patients with systemic sclerosis had a prolonged Tp-e interval and Tp-e/QT ratio compared with healthy subjects. Furthermore, this prolongation was well correlated with clinical severity score among patients with systemic sclerosis [2].…”
mentioning
confidence: 79%
“…We would like to thank the authors for the letter [1] regarding our manuscript entitled "Prolonged Tp-e interval and Tp-e/QT correlates well with modified Rodnan skin severity score in patients with systemic sclerosis" [2] published in "Cardiology Journal". We would also like to thank the Editor for the opportunity to respond to this letter.…”
mentioning
confidence: 99%